Comparative phylogeography in the Atlantic forest and Brazilian savannas: pleistocene fluctuations and dispersal shape spatial patterns in two bumblebees. Issue 1 (December 2016) - Françoso, Elaine; Zuntini, Alexandre; Carnaval, Ana; Arias, Maria
Abstract Background Bombus morio andB. pauloensis are sympatric widespread bumblebee species that occupy two major Brazilian biomes, the Atlantic forest and the savannas of the Cerrado. Differences in dispersion capacity, which is greater inB. morio, likely influence their phylogeographic patterns. This study asks which processes best explain the patterns of genetic variation observed inB. morio andB. pauloensis, shedding light on the phenomena that shaped the range of local populations and the spatial distribution of intra-specific lineages. Results Results suggest that Pleistocene climatic oscillations directly influenced the population structure of both species. Correlative species distribution models predict that the warmer conditions of the Last Interglacial contributed to population contraction, while demographic expansion happened during the Last Glacial Maximum. These results are consistent with physiological data suggesting that bumblebees are well adapted to colder conditions. Intra-specific mitochondrial genealogies are not congruent between the two species, which may be explained by their documented differences in dispersal ability. Conclusions While populations of the high-dispersalB. morio are morphologically and genetically homogeneous across the species range, B. pauloensis encompasses multiple (three) mitochondrial lineages, and show clear genetic, geographic, and morphological differences. Because the lineages ofB. pauloensis are currently exposed to distinct climatic conditions (and elevations), parapatric diversification may occur within this taxon. The eastern portion of the state of São Paulo, the most urbanized area in Brazil, represents the center of genetic diversity forB. pauloensis.